Riset kebijakan publikasi repositori institusi Perguruan Tinggi Keagamaan Islam Negeri Indonesia - Nurohman, Aris (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2024)
Building and developing an institutional repository by Islamic Religious Colleges in Indonesia aims to accommodate, process and disseminate or publish online so that it can be used in ongoing scientific communication. In fact, there are many models of publishing repository content among state Islamic religious universities in Indonesia, so that is the reason for the need to study the publication policies that are applied. This research uses a descriptive analysis method with a mixed method approach. Quantitative methods are used to map the number of institutions that are used as research objects. Qualitative methods were applied in the analysis of the collected data. The study was carried out between March 2022 and July 2022. Data analysis was carried out by interpreting the data obtained from interviews with informants, reinforced by data from documentation and observations. Based on an in-depth study, the researchers found that there are 3 publication models among institutional repository managers, namely open access, closed access and limited access models. The background to the diversity of repository publication models is the lack of integrated management support between institutional leaders, faculties and libraries in institutional repository management.